ANALISIS KENDALA PESERTA DIDIK DALAM MEMAHAMI KONSEP INTEGRASI PEMBELAJARAN IPAS KELAS IV SD NEGERI KLAMPOK 01 - Nur Oktaviani, An Nisa; Toharudin, Moh; Muamar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study employed a descriptive qualitative approach aimed at providing an in- depth description of the challenges experienced by students in understanding the integrated concept of IPAS (Science and Social Studies) learning in Grade 4 at SD Negeri Klampok 01. Referring to the current situation, after conducting observations and interviews with one of the Grade 4 teachers at SD Negeri Klampok 01 who has implemented the IPAS subject under the Merdeka Curriculum, several challenges were identified in delivering integrated IPAS instruction. The data collection techniques used in this study included interviews, observations, and documentation. Based on the findings, it was revealed that students continue to face difficulties in distinguishing and understanding the connection between Natural Science (IPA) and Social Science (IPS) materials presented in an integrated format. These challenges fall into two categories: internal and external obstacles.